Can we learn from benchmarking studies of airports and where do we want to go from here? - Jürgen Müller; Vanessa Kamp; Hans-Martin Niemeier (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2005)
This paper outlines some first results from a study on the technical efficiency and total factor productivity (TFP) of 17 international airports in Germany. The analysis was undertaken with panel data from 1998 - 2002. According to the Malmquist-DEA the performance at nearly every airport decreased from 2001, mainly due to the aftermath of September 11, 2001. As was assumed, the technical efficiency and productivity of most airports declined. This was especially the case for the terminal side since capacity expansions in the form of new or additional terminal buildings increased excess supply while passenger volume was decreasing. This study is the first step of a larger research project on measuring the performance of German airports.
Keywords: 650